2019
DOI: 10.1038/s41598-019-44664-8
|View full text |Cite|
|
Sign up to set email alerts
|

The association between physical activity and low back pain: a systematic review and meta-analysis of observational studies

Abstract: The aim of this review was to investigate the association between total and domain-specific physical activity (PA) and non-specific low back pain (LBP) in adults. Seven databases were searched for cohort and cross-sectional studies. Pooled estimates of the association of medium and high levels PA and LBP, using the generic inverse-variance method with fixed- and random-effects models were calculated. Twenty-four studies (15 cohort and nine cross-sectional; 95,796 participants) were included. The pooled fully a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
84
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 63 publications
(113 reference statements)
10
84
3
5
Order By: Relevance
“…Literatures stated that the 12-month prevalence of LBP among nursing personnel is estimated to be up to 65% [45]. The result of the present systematic review and meta-analysis also showed that the overall 12month prevalence of LBP among nurses was 64.07%.…”
Section: Discussionsupporting
confidence: 65%
“…Literatures stated that the 12-month prevalence of LBP among nursing personnel is estimated to be up to 65% [45]. The result of the present systematic review and meta-analysis also showed that the overall 12month prevalence of LBP among nurses was 64.07%.…”
Section: Discussionsupporting
confidence: 65%
“…These findings emphasize that inactivity may play a greater role as a risk factor for prolonged disability, and that high activity levels might not automatically play a protective role. Medium activity level was associated with lower prevalence of LBP according a systematic review, while the association between high activity level and LBP, compared to low activity level, was not clear 37 . In a large prospective study consisting of older adults, high-risk individuals, as classified according to 11 biopsychosocial risk factors, were three times more likely to develop pain compared to low-risk group 38 .…”
Section: Discussionmentioning
confidence: 89%
“…In a systematic review and meta-analysis, it was found that when cohort studies were considered, people who practiced a medium level of PA had a 10% lower risk of CBP lumbar (p = 0.0009). When cross-sectional studies were considered, the association suggested 7% decreased odds, but it was not significant (p = 0.68) [44].…”
Section: Discussionmentioning
confidence: 94%